2019
DOI: 10.1016/j.jmbbm.2018.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Wear and Friction of UHMWPE-on-PEEK OPTIMA™

Abstract: PEEK-OPTIMA™ is being considered as an alternative bearing material to cobalt chrome in the femoral component of total knee replacement to provide a metal-free implant. The aim of this study was to investigate the influence of lubricant temperature (standard rig running and elevated temperature (~36 °C)) on the wear of a UHMWPE-on-PEEK OPTIMA™ bearing couple using different lubricant protein concentrations (0%, 2%, 5%, 25% and 90% bovine serum) in a simple geometry pin-on-plate configuration. Friction was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 51 publications
(79 reference statements)
3
37
0
1
Order By: Relevance
“…When compared to control tests carried out against smooth plates, the damage simulation protocol used in this study did not generate scratches with a lip height of sufficient magnitude to influence the wear of UHMWPE against either damaged PEEK or CoCr plates. The wear factor of the UHMWPE pins in the control study was similar to that previously reported under comparable conditions [8]. It is interesting to note that the variability in the data was consistently larger in the UHMWPE-on-PEEK bearing couple compared to UHMWPE-on-CoCr and that following third body damage simulation, the variability in the data was further increased for both material combinations.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…When compared to control tests carried out against smooth plates, the damage simulation protocol used in this study did not generate scratches with a lip height of sufficient magnitude to influence the wear of UHMWPE against either damaged PEEK or CoCr plates. The wear factor of the UHMWPE pins in the control study was similar to that previously reported under comparable conditions [8]. It is interesting to note that the variability in the data was consistently larger in the UHMWPE-on-PEEK bearing couple compared to UHMWPE-on-CoCr and that following third body damage simulation, the variability in the data was further increased for both material combinations.…”
Section: Discussionsupporting
confidence: 86%
“…The plate was mounted in a lubricant-containing bath, which reciprocated over a length of 20 mm at 1Hz, and as the bath reciprocated, the UHMWPE pin rotated (±20 • ) via a rack and pinion mechanism. a constant axial load of 160 N was applied through the pin (8 mm flat contact face) to give an average contact pressure of 3.18 MPa consistent with previous wear simulation of the UHMWPE-on-PEEK bearing couple [8]. All wear simulation studies were carried out using 25% bovine serum supplemented with 0.03% sodium azide solution as a lubricant and were carried out under rig running (room) temperature conditions as previously described and optimised for the UHMWPE-on-PEEK bearing couple [8].…”
Section: Pin-on-plate Wear Simulationmentioning
confidence: 54%
See 3 more Smart Citations